Superadditive and subadditive transformations of integrals and aggregation functions - Greco, Salvatore; Mesiar, Radko; Rindone, Fabio; Šipeky, Ladislav (Fuzzy sets and systems, 2016)
We propose the concepts of superadditive and of subadditive transformations of aggregation functions acting on non-negative reals, in particular of integrals with respect to monotone measures. We discuss special properties of the proposed transforms and links between some distinguished integrals. Superadditive transformation of the Choquet integral, as well as of the Shilkret integral, is shown to coincide with the corresponding concave integral recently introduced by Lehrer. Similarly the transformation of the Sugeno integral is studied. Moreover, subadditive transformation of distinguished integrals is also discussed.